Tryptamine 5-Hydroxylase Is Required for Suppression of Cell Death and Uncontrolled Defense Activation in Rice - Shen, Wangxin; Feng, Zhiming; Hu, Keming; Cao, Wenlei; Li, Mengchen; Ju, Ran; Zhang, Yafang; Chen, Zongxiang; Zuo, Shimin (Frontiers in Sustainable Food Systems, 2022)
Lesion-mimic mutants are useful materials to dissect mechanisms controlling programmed cell death (PCD) and defense response in plants. Although dozens of lesion-mimic mutant genes have been identified in plants, the molecular mechanisms underlying PCD and defense response remain to be extensively elucidated. Here, we identified a rice lesion mimic mutant, named lesion mimic 42 (lm42), from an ethylmethylsulfone (EMS)-induced mutant population. The lm42 mutant displayed flame-red spots on the leaves and sheaths at the 3-leaf developmental stage and exhibited impaired photosynthetic capacity with decreased chlorophyll content and decomposed chloroplast thylakoids. The lesion development of lm42 was light- and temperature-dependent. We identified a single base mutation (T38A), changing a Leu to Gln, in the first exon of LOC_Os12g16720 (LM42), which encodes a tryptamine 5-hydroxylase, by map-based cloning. We carried out transgenic complementation to confirm that this mutation caused the lm42 phenotype. We further knocked out the LM42 gene by CRISPR/Cas9 to recreate the lm42 phenotype. LM42 is highly expressed in leaves, leaf sheaths and roots. Loss-of-function of LM42 activated expression of ROS-generating genes and inhibited expression of ROS-scavenging genes, leading to ROS accumulation and eventually cell death. Furthermore, its disruption induced expression of defense-response genes and enhanced host resistance to both fungal pathogen Magnaporthe oryzae and bacterial pathogen Xanthomonas oryzae pv. oryzae. Our transcriptomic data suggested that the way lm42 led to lesion-mimic was probably by affecting ribosome development. Overall, our results demonstrate that tryptamine 5-hydroxylase-coding gene LM42 is required for suppression of cell death and uncontrolled activation of defense responses in rice.